The Garn pattern profile analysis on personal computers - Brown Tasman; Travan George R. (Sciendo, 1988)
Pattern profile analysis is a method for quantifying craniofacial morphology from standardised cephalograms. This implementation on personal computers adheres closely to the description of Garn with respect to the reference points and linear variables used in the analysis. The program provides a multicolour output by plotter which summarises the morphological pattern and displays the extent of patterning in comparison with sex - and age-specific standards from the University of Michigan growth study. The procedures are illustrated by analyses of subjects with Turner and Binder's syndromes. Pattern profile analysis is a useful diagnostic aid in clinical fields which require an evaluation of craniofacial relationships.